Economic Impact of Tibial Plateau Leveling Osteotomy Surgical Site Infection in Dogs. Issue 8 (11th March 2014) - Nicoll, Catherine; Singh, Ameet; Weese, J. Scott
<x xml:space="preserve">Abstract</x> Objective To evaluate the economic impact of surgical site infection after tibial plateau leveling osteotomy (TPLO) in dogs. Study Design Retrospective study Study Population Dogs that had unilateral TPLO and did (n = 32) or did not (controls; 32) develop a surgical site infection. Methods Medical and billing records were reviewed to identify postoperative care and costs, which were compared between groups. Results Age, weight, gender, and initial surgical costs did not differ between groups. Postoperative costs were higher for dogs that developed SSIs ($1559) than for controls ($212, P < .0001), as were number of postoperative recheck visits (P < .0001) and time until final case closure (P = .0002). Dogs with surgical site infection (SSI) returned for a mean (±SD) 4.1 ± 2.9 (range, 1–13) postoperative visits attributable to SSI management: mean outpatient visits 3.0 ± 2.5; mean inpatient stays, 1.2 ± 0.74; and mean hospitalization, 4.3 ± 4.1 days. Postoperative costs attributable to SSI management ranged from $145 to $5022. Implants were removed in 22 (69%) dogs with SSIs. Bacteria were isolated from the surgical site or implant of 23 (72%) dogs with SSIs. There was a significant difference in cost when bacteria were isolated ($1836 versus $853, P = .002), but no impacts on likelihood of implant removal (16/23, 70% versus 6/9, 67%, P = 0.87). Staphylococcus pseudintermedius was predominant. Conclusions SSI after TPLO are associated with a significant cost. These data help quantify those costs, to facilitate a greater understanding of the impact of SSI, and the need for infection control.